Genome-Wide Identification, Evolution, and Expression Analysis of LBD Transcription Factor Family in Bread Wheat (Triticum aestivum L.) - Wang, Zhenyu; Zhang, Ruoyu; Cheng, Yue; Lei, Pengzheng; Song, Weining; Zheng, Weijun; Nie, Xiaojun (Frontiers in Plant Science, 2021)
The lateral organ boundaries domain (LBD) genes, as the plant-specific transcription factor family, play a crucial role in controlling plant architecture and stress tolerance. Although it has been thoroughly characterized in many species, the LBD family was not well studied in wheat. Here, the wheat LBD family was systematically investigated through an in silico genome-wide search method. A total of 90 wheat LBD genes (TaLBDs) were identified, which were classified into class I containing seven subfamilies, and class II containing two subfamilies. Exon–intron structure, conserved protein motif, and cis-regulatory elements analysis showed that the members in the same subfamily shared similar gene structure organizations, supporting the classification. Furthermore, the expression patterns of these TaLBDs in different types of tissues and under diverse stresses were identified through public RNA-seq data analysis, and the regulation networks of TaLBDs involved were predicted. Finally, the expression levels of 12 TaLBDs were validated by quantitative PCR (qPCR) analysis and the homoeologous genes showed differential expression. Additionally, the genetic diversity of TaLBDs in the landrace population showed slightly higher than that of the genetically improved germplasm population while obvious asymmetry at the subgenome level. This study not only provided the potential targets for further functional analysis but also contributed to better understand the roles of LBD genes in regulating development and stress tolerance in wheat and beyond.